Thermoplastic resin composition and molded article comprising same
By using acid phosphate and inorganic filler/flame retardant with specific acid values in thermoplastic resins, the problem of discoloration and strength reduction of thermoplastic resins under severe conditions is solved, and high temperature molding and excellent recycling and utilization are achieved.
Patent Information
- Application Number
- CN202380067571.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-22
- Filing Date
- 2023-08-23
- Publication Date
- 2025-05-02
AI Technical Summary
The conventional thermoplastic resin compositions are prone to discoloration and decrease in strength under severe processing conditions, and their recycling properties are poor.
The thermal stability of the composition is improved, discoloration and strength reduction is prevented, while improving its recycling property by adding acid phosphate esters with specific acid values to the thermoplastic resin and combined with inorganic filler materials and/or flame retardants.
The thermoplastic resin composition with discoloration and less intensity reduction under severe processing conditions is achieved, and has excellent recyclability and is suitable for application scenarios where high temperature molding and reusability are required.
Smart Images

Figure BDA0005320837750000071 
Figure BDA0005320837750000081 
Figure BDA0005320837750000082
Abstract
Description
Technical Field
[0001] The present invention relates to a thermoplastic resin composition that has little discoloration and strength reduction during molding and a molded product made of the composition. More specifically, it relates to a thermoplastic resin composition that has little discoloration and strength reduction under severe processing conditions and has excellent recyclability and a molded product made of the composition. Background Art
[0002] Thermoplastic resin compositions are used in a wide range of fields such as housings and parts of electrical, electronic and OA equipment, interior and exterior parts for automobiles, furniture, musical instruments, and sundries. In recent years, in order to achieve a sustainable society, it is hoped that thermoplastic resin compositions have high recyclability. On the other hand, it is well known that thermoplastic resin compositions use phosphorus compounds as heat stabilizers. Patent document 1 discloses the use of specific phosphorus compounds in resins composed of polycarbonate resins and polyester resins. Patent document 2 discloses the use of phosphorus compounds in combination. However, the thermal stability during molding processing in existing methods is still insufficient, and there is a trend that molding conditions become high temperatures in applications that particularly require thin walls and lightweight, and the number of cases where thermal stability is insufficient increases. In addition, the demand for recycling products is also high, and it is suggested that the demand for materials that can meet the requirements of thermoplastic resin compositions that do not discolor, reduce strength, and have excellent recyclability even under harsh processing conditions is increasing.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 4983427
[0006] Patent Document 2: Japanese Patent No. 5640734 Summary of the invention
[0007] An object of the present invention is to provide a thermoplastic resin composition which has little discoloration and strength reduction even under severe processing conditions and is excellent in recyclability, and a molded article composed of the composition.
[0008] The present inventors have conducted intensive studies to achieve the above-mentioned purpose, and as a result, have found that by adding an acidic phosphate ester having a specific acid value to a thermoplastic resin, a thermoplastic resin composition having less discoloration and strength reduction and excellent recyclability even under severe processing conditions and a molded article composed of the composition can be provided, thereby completing the present invention. In another embodiment, it has been found that by adding an inorganic filler and / or a flame retardant in addition to the acidic phosphate ester having a specific acid value, a thermoplastic resin composition having not only prevented discoloration and strength reduction but also improved rigidity or flame retardancy and a molded article composed of the composition can be provided.
[0009] That is, the present invention is as follows.
[0010] 1. A thermoplastic resin composition comprising 0.001 to 1 part by weight of (B) an acidic phosphate ester having an acid value of 10 to 200 mgKOH / g (component B) based on 100 parts by weight of (A) a thermoplastic resin (component A).
[0011] 2. The thermoplastic resin composition according to the above item 1, further comprising 1 to 150 parts by weight of (C) an inorganic filler (component C) based on 100 parts by weight of the component A.
[0012] 3. The thermoplastic resin composition according to the above item 1 or 2, further comprising 0.01 to 25 parts by weight of a flame retardant (component D) based on 100 parts by weight of the component A.
[0013] 4. The thermoplastic resin composition according to any one of the above items 1 to 3, further comprising 0.05 to 3 parts by weight of (E) an anti-dripping agent (component E) based on 100 parts by weight of component A.
[0014] 5. The thermoplastic resin composition according to any one of the preceding items 1 to 4, wherein component A is at least one thermoplastic resin selected from the group consisting of (A-1) polycarbonate resin (component A-1), (A-2) ABS resin (component A-2), (A-3) polyester resin (component A-3), (A-4) AS resin (component A-4), (A-5) PS resin (component A-5), and (A-6) AAS resin (component A-6).
[0015] 6. The thermoplastic resin composition according to any one of the above items 1 to 5, wherein component A is at least one thermoplastic resin selected from the group consisting of (A-1) polycarbonate resin (component A-1), (A-2) ABS resin (component A-2), and (A-3) polyester resin (component A-3).
[0016] 7. The thermoplastic resin composition according to any one of the above items 1 to 6, wherein the content of the component A-1 is 40 to 100 parts by weight in 100 parts by weight of the component A.
[0017] 8. The thermoplastic resin composition according to any one of the above Items 1 to 7, wherein the component B is stearyl acid phosphate.
[0018] 9. The thermoplastic resin composition according to any one of the preceding items 1 to 8, wherein the component C is at least one inorganic filler selected from the group consisting of (C-1) glass fiber (component C-1), (C-2) plate-shaped glass filler (component C-2), (C-3) fibrous carbon filler (component C-3), (C-4) non-fibrous carbon filler (component C-4), and (C-5) silicate mineral (component C-5).
[0019] 10. The thermoplastic resin composition according to any one of the preceding items 1 to 9, wherein the component D is at least one flame retardant selected from the group consisting of (D-1) a halogenated carbonate compound (component D-1), (D-2) a phosphate ester compound (component D-2), (D-3) a phosphazene compound (component D-3), (D-4) a metal sulfonate (component D-4), and (D-5) an organosilicon compound (component D-5).
[0020] 11. A molded article comprising the thermoplastic resin composition according to any one of 1 to 10 above.
[0021] The thermoplastic resin composition of the present invention is a thermoplastic resin composition that has little discoloration and strength reduction under severe processing conditions and is also excellent in recyclability. Therefore, it is useful in applications requiring thin-wall and lightweight molding conditions at high temperatures and in the case of recycling products, and has a great industrial effect. DETAILED DESCRIPTION
[0022] Hereinafter, the present invention will be described in detail.
[0023] <Component A: Thermoplastic resin>
[0024] The thermoplastic resin used as component A of the present invention is polycarbonate resin, ABS resin, polyester resin, AS resin, PS resin, AAS resin, AES resin, polyamide resin, polyolefin resin, fluorine resin, PPS resin, PEEK resin, polyarylate resin, polyacetal resin, etc., preferably at least one thermoplastic resin selected from polycarbonate resin, ABS resin, polyester resin, AS resin, PS resin and AAS resin. In addition, component A is at least one thermoplastic resin selected from polycarbonate resin, ABS resin and polyester resin, and more preferably the content of polycarbonate resin is 40 to 100 parts by weight in 100 parts by weight of component A. It should be noted that the content of polycarbonate resin is more preferably 60 to 100 parts by weight in 100 parts by weight of component A.
[0025] <Component A-1: Polycarbonate resin>
[0026] The polycarbonate resin used as the component A-1 of the present invention is obtained by reacting a dihydric phenol with a carbonate precursor. Examples of the reaction method include interfacial polymerization, melt transesterification, solid phase transesterification of carbonate prepolymers, and ring-opening polymerization of cyclic carbonate compounds.
[0027] Representative examples of the dihydric phenols used herein include hydroquinone, resorcinol, 4,4'-biphenol, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, The preferred dihydric phenols include bis(4-hydroxyphenyl)-4-isopropylcyclohexane, bis(4-hydroxyphenyl)-oxygen ether, bis(4-hydroxyphenyl)-sulfide, bis(4-hydroxyphenyl)-sulfoxide, bis(4-hydroxyphenyl)-sulfone, bis(4-hydroxyphenyl)-ketone, bis(4-hydroxyphenyl)-ester, bis(4-hydroxy-3-methylphenyl)-sulfide, 9,9-bis(4-hydroxyphenyl)-fluorene, and 9,9-bis(4-hydroxy-3-methylphenyl)-fluorene. Preferred dihydric phenols are bis(4-hydroxyphenyl)-alkanes, and among them, bisphenol A is particularly preferred from the viewpoint of impact resistance and is widely used.
[0028] In the present invention, in addition to the general-purpose polycarbonate resin, i.e., bisphenol A-based polycarbonate resin, a special polycarbonate resin produced using other dihydric phenols may be used as the A-1 component. For example, a polycarbonate resin (homopolymer or copolymer) obtained by using 4,4'-(m-phenylene diisopropylidene) diphenol (hereinafter sometimes referred to as "BPM"), 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (hereinafter sometimes referred to as "Bis-TMC"), 9,9-bis(4-hydroxyphenyl)fluorene and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene (hereinafter sometimes referred to as "BCF") as part or all of the dihydric phenol components is suitable for applications where the requirements for dimensional change and morphological stability due to water absorption are particularly strict. These dihydric phenols other than BPA are preferably used in an amount of 5 mol% or more, particularly 10 mol% or more of all the dihydric phenol components constituting the polycarbonate resin. In particular, when high rigidity and better hydrolysis resistance are required, it is particularly preferred that the component A constituting the resin composition is a copolymerized polycarbonate resin of the following (1) to (3).
[0029] (1) A copolymerized polycarbonate resin in which BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and BCF is 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %) in 100 mol % of the dihydric phenol component constituting the polycarbonate resin.
[0030] (2) A copolymerized polycarbonate resin in which BPA accounts for 10 to 95 mol % (more preferably 50 to 90 mol %, and even more preferably 60 to 85 mol %) and BCF accounts for 5 to 90 mol % (more preferably 10 to 50 mol %, and even more preferably 15 to 40 mol %) in 100 mol % of the dihydric phenol component constituting the polycarbonate resin.
[0031] (3) A copolymerized polycarbonate resin in which BPM accounts for 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and Bis-TMC accounts for 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %) in 100 mol % of the dihydric phenol component constituting the polycarbonate resin.
[0032] These special polycarbonate resins can be used alone or in combination of two or more thereof. In addition, they can be mixed with a general bisphenol A type polycarbonate resin. The preparation methods and properties of these special polycarbonate resins are described in detail in, for example, Japanese Patent Publication No. 6-172508, Japanese Patent Publication No. 8-27370, Japanese Patent Publication No. 2001-55435, and Japanese Patent Publication No. 2002-117580.
[0033] Among the various polycarbonate resins mentioned above, polycarbonate resins whose copolymerization composition is adjusted so that the water absorption and Tg (glass transition temperature) are within the following ranges are particularly suitable for fields requiring morphological stability because the polymer itself has good hydrolysis resistance and is also particularly excellent in low warpage after molding.
[0034] (i) a polycarbonate resin having a water absorption of 0.05 to 0.15%, preferably 0.06 to 0.13%, and a Tg of 120 to 180°C, or
[0035] (ii) A polycarbonate resin having a Tg of 160 to 250°C, preferably 170 to 230°C, and a water absorption of 0.10 to 0.30%, preferably 0.13 to 0.30%, more preferably 0.14 to 0.27%.
[0036] Here, the water absorption of the polycarbonate resin is a value obtained by measuring the moisture content of a disk-shaped test piece having a diameter of 45 mm and a thickness of 3.0 mm after immersion in water at 23° C. for 24 hours in accordance with ISO 62-1980. In addition, Tg (glass transition temperature) is a value obtained by differential scanning calorimetry (DSC) in accordance with JIS K7121.
[0037] As the carbonate precursor, carbonyl halide, carbonic acid diester, halogenated formates, etc. can be used, and specific examples thereof include phosgene, diphenyl carbonate, and dihalogenated formates of dihydric phenols.
[0038] When utilizing interfacial polymerization to manufacture polycarbonate resin with above-mentioned dihydric phenol and carbonate precursor, can use catalyst, end-capping agent, antioxidant that is used to prevent dihydric phenol oxidation etc. as required.In addition, polycarbonate resin of the present invention comprises: the branched polycarbonate resin obtained by copolymerization of polyfunctional aromatic compounds above trifunctional, the polyester carbonate resin obtained by copolymerization of difunctional carboxylic acid of aromatic or aliphatic (comprising alicyclic), the copolymerization polycarbonate resin obtained by copolymerization of difunctional alcohol (comprising alicyclic), and the polyester carbonate resin obtained by copolymerization of above-mentioned difunctional carboxylic acid and difunctional alcohol.In addition, can also be the mixture that more than 2 kinds of the polycarbonate resin that obtains are mixed.
[0039] The branched polycarbonate resin can impart anti-drip properties to the thermoplastic resin composition of the present invention. Examples of the trifunctional or higher polyfunctional aromatic compound used in the branched polycarbonate resin include phloroglucinol, pentahydroxybiphenyl, or 4,6-dimethyl-2,4,6-tris(4-hydroxydiphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylbenzyl The present invention can be used in combination with any of the foregoing inventions and / or the invention can be used to prepare trisphenols such as 4-{4-[1,1-bis(4-hydroxyphenyl)ethyl]benzene}-α,α-dimethylbenzylphenol, tetrakis(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, or trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.
[0040] The amount of the constituent units derived from the polyfunctional aromatic compound in the branched polycarbonate resin is preferably 0.01 to 1 mol%, more preferably 0.05 to 0.9 mol%, and further preferably 0.05 to 0.8 mol%, in the total of 100 mol% of the constituent units derived from the dihydric phenol and the constituent units derived from the polyfunctional aromatic compound. In addition, in particular, in the case of the melt transesterification method, branched structural units may be generated as a side reaction, and the amount of the branched structural units is also preferably 0.001 to 1 mol%, more preferably 0.005 to 0.9 mol%, and further preferably 0.01 to 0.8 mol%, in the total of 100 mol% of the constituent units derived from the dihydric phenol. It should be noted that the proportion of the branched structure can be adjusted by 1 It was calculated by H-NMR measurement.
[0041] The aliphatic difunctional carboxylic acid is preferably an α,ω-dicarboxylic acid. As the aliphatic difunctional carboxylic acid, for example, a straight-chain saturated aliphatic dicarboxylic acid such as sebacic acid (decane dioic acid), dodecanedioic acid, tetradecanedioic acid, octadecanedioic acid, eicosanedioic acid, and an alicyclic dicarboxylic acid such as cyclohexane dicarboxylic acid can be preferably mentioned. As the difunctional alcohol, an alicyclic diol is more preferably used, and for example, cyclohexanedimethanol, cyclohexanediol, and tricyclodecanedimethanol can be exemplified.
[0042] Reaction forms such as the interfacial polymerization method, the melt transesterification method, the carbonate prepolymer solid phase transesterification method and the ring-opening polymerization method of a cyclic carbonate compound as the production method of the polycarbonate resin of the present invention are methods fully disclosed in various documents and Japanese Patent Gazettes.
[0043] When manufacturing the thermoplastic resin composition of the present invention, the viscosity average molecular weight of the polycarbonate resin is preferably 12500 to 32000, more preferably 16000 to 28000, and further preferably 18000 to 26000. When a polycarbonate resin having a viscosity average molecular weight of less than 12500 is used, good mechanical properties may not be obtained. On the other hand, a resin composition obtained from a polycarbonate resin having a viscosity average molecular weight exceeding 32000 may have poor molding processability.
[0044] The viscosity average molecular weight in the present invention is first determined by using an Ostwald viscometer to obtain a specific viscosity (ηSP) calculated from a solution prepared by dissolving 0.7 g of polycarbonate in 100 ml of dichloromethane at 20° C.:
[0045] Specific viscosity (ηSP) = (t-t0) / t0
[0046] [t0 is the dripping seconds of dichloromethane, t is the dripping seconds of the sample solution]
[0047] The viscosity average molecular weight M is calculated from the determined specific viscosity (ηSP) according to the following mathematical formula.
[0048] ηSP / c=[η]+0.45×[η] 2 c (where [η] is limiting viscosity)
[0049] [η] = 1.23 × 10 -4 M 0.83
[0050] c=0.7
[0051] It should be noted that the viscosity average molecular weight of the polycarbonate resin in the thermoplastic resin composition of the present invention is calculated according to the following procedure. That is, the composition is mixed with 20 to 30 times its weight of dichloromethane to dissolve the soluble components in the composition. The above-mentioned soluble components are filtered through diatomaceous earth and collected. Then the solvent in the obtained solution is removed. The solid after the solvent is removed is fully dried to obtain a solid of the component dissolved in dichloromethane. The specific viscosity at 20°C is calculated in the same way as above from a solution obtained by dissolving 0.7 g of the above-mentioned solid in 100 ml of dichloromethane, and the viscosity average molecular weight M is calculated in the same way as above from the specific viscosity.
[0052] A polycarbonate-polydiorganosiloxane copolymer resin may also be used as the polycarbonate resin of the present invention. The polycarbonate-polydiorganosiloxane copolymer resin is preferably a copolymer resin prepared by copolymerizing a dihydric phenol represented by the following general formula (1) and a hydroxyaryl-terminated polydiorganosiloxane represented by the following general formula (3).
[0053]
[0054] [In the above general formula (1), R 1 and R 2 Each independently represents a group selected from a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group and a carboxyl group; when there are plural groups, they may be the same or different; e and f are each an integer of 1 to 4; and W is a single bond or at least one group selected from the groups represented by the following general formula (2).]
[0055]
[0056] [In the above general formula (2), R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 and R 18 Each independently represents a group selected from a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms, and R 19 and R 20 Each independently represents a group selected from a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkyloxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group and a carboxyl group. When a plurality of these groups exist, they may be the same or different. g is an integer of 1 to 10, and h is an integer of 4 to 7.]
[0057]
[0058] [In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms, R 9 and R 10Each is independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number from 10 to 300. X is a divalent aliphatic group having 2 to 8 carbon atoms.]
[0059] Examples of the dihydric phenol (I) represented by the general formula (1) include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxy-3,3'-biphenyl)propane, 2,2-bis(4-hydroxy-3-isopropylphenyl)propane, 2,2 bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(3-bromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)diphenylmethane, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxyphenyl) (4-Hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyl diphenyl ether, 4,4'-sulfonyl diphenol, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide, 2,2'-dimethyl-4,4'-sulfonyl diphenol, 4,4'-dihydroxy-3,3'-dimethyl diphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyl diphenyl sulfide, 2,2'-diphenyl-4,4'-sulfonyl diphenol, 4,4 '-Dihydroxy-3,3'-diphenyl diphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyl diphenyl sulfide, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis(4-hydroxyphenyl)cyclohexane, 1,3-bis(4-hydroxyphenyl)cyclohexane, 4,8-bis(4-hydroxyphenyl)tricyclo[5.2.1.02,6]decane, 4,4'-(1,3-adamantanediyl)diphenol, 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane, etc.
[0060] Among them, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferred, and 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are particularly preferred. Among them, 2,2-bis(4-hydroxyphenyl)propane is most preferred because of its excellent strength and durability. In addition, these may be used alone or in combination of two or more.
[0061] As the hydroxyaryl-terminated polydiorganosiloxane represented by the general formula (3), for example, the following compounds can be suitably used.
[0062]
[0063] Hydroxyaryl-terminated polydiorganosiloxane (II) can be easily produced by subjecting phenols having ethylenically unsaturated carbon-carbon bonds, preferably vinylphenol, 2-allylphenol, isopropenylphenol, 2-methoxy-4-allylphenol, to hydrosilylation reaction with the end of a polysiloxane chain having a predetermined degree of polymerization. Among them, (2-allylphenol)-terminated polydiorganosiloxane and (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane are preferred, and (2-allylphenol)-terminated polydimethylsiloxane and (2-methoxy-4-allylphenol)-terminated polydimethylsiloxane are particularly preferred. Hydroxyaryl-terminated polydiorganosiloxane (II) preferably has a molecular weight distribution (Mw / Mn) of 3 or less. In order to further exhibit excellent low outgassing properties and low-temperature impact properties during high-temperature molding, the above molecular weight distribution (Mw / Mn) is more preferably 2.5 or less, and more preferably 2 or less. If the upper limit of the above preferred range is exceeded, the amount of outgassing generated during high temperature molding may be large and the low temperature impact resistance may be poor.
[0064] In order to achieve high impact resistance, the diorganosiloxane polymerization degree (p+q) of the hydroxyaryl-terminated polydiorganosiloxane (II) is preferably 10 to 300. The diorganosiloxane polymerization degree (p+q) is preferably 10 to 200, more preferably 12 to 150, and further preferably 14 to 100. When the degree of polymerization is less than the lower limit of the preferred range, the impact resistance that is a characteristic of the polycarbonate-polydiorganosiloxane copolymer cannot be effectively exhibited, and when the degree of polymerization exceeds the upper limit of the preferred range, appearance defects occur.
[0065] The content of polydiorganosiloxane in the total weight of the polycarbonate-polydiorganosiloxane copolymer resin used in component A-1 is preferably 0.1 to 50% by weight. The content of the polydiorganosiloxane component is more preferably 0.5 to 30% by weight, and further preferably 1 to 20% by weight. When it is above the lower limit of the preferred range, the impact resistance and flame retardancy are excellent, and when it is below the upper limit of the preferred range, it is easy to obtain a stable appearance that is not easily affected by molding conditions. The degree of polymerization of the polydiorganosiloxane and the content of the polydiorganosiloxane can be determined by 1 It was calculated by H-NMR measurement.
[0066] In the present invention, the hydroxyaryl-terminated polydiorganosiloxane (II) may be used alone or in combination of two or more.
[0067] Furthermore, other comonomers other than the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) may be used in an amount of 10% by weight or less based on the total weight of the copolymer within a range not hindering the present invention.
[0068] In the present invention, a mixed solution containing an oligomer having a terminal chloroformate group is prepared by reacting a dihydric phenol (I) with a carbonate-forming compound in a mixed solution of a water-insoluble organic solvent and an aqueous alkali solution.
[0069] When generating the oligomer of dihydric phenol (I), the dihydric phenol (I) used in the method of the present invention can be made into oligomers all at once, or a part of it and the post-added monomer can be added as reaction raw materials in the subsequent interfacial polycondensation reaction. The post-added monomer is added in order to quickly carry out the subsequent polycondensation reaction, and does not need to be intentionally added when it is not necessary.
[0070] The method of the oligomer formation reaction is not particularly limited, but is usually preferably a method in which the reaction is carried out in a solvent in the presence of an acid binder.
[0071] The ratio of the carbonate-forming compound to be used may be appropriately adjusted in consideration of the stoichiometric ratio (equivalent) of the reaction. In the case of using a gaseous carbonate-forming compound such as phosgene, a method of blowing it into the reaction system may be appropriately adopted.
[0072] As the above-mentioned acid binder, for example, organic bases such as alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, alkali metal carbonates such as sodium carbonate, potassium carbonate, pyridine or their mixtures etc. can be used. The usage ratio of the acid binder also considers the stoichiometric ratio (equivalent) of the reaction in the same manner as above and appropriately determines. Specifically, it is preferred to use 2 equivalents or a slightly excessive acid binder compared with the mole number (usually 1 mole is equivalent to 2 equivalents) of the dihydric phenol (I) used for the formation of the oligomer.
[0073] As the above-mentioned solvent, any solvent inactive to various reactions, such as the solvent used in the manufacture of known polycarbonates, may be used alone or as a mixed solvent. Representative examples include hydrocarbon solvents such as xylene, halogenated hydrocarbon solvents represented by methylene chloride and chlorobenzene, and the like. It is particularly preferred to use halogenated hydrocarbon solvents such as methylene chloride.
[0074] The reaction pressure for oligomer formation is not particularly limited and may be any of normal pressure, pressurized, and reduced pressure. It is generally advantageous to conduct the reaction under normal pressure. The reaction temperature is selected from the range of -20 to 50°C. In many cases, heat is generated with polymerization, so water cooling or ice cooling is preferred. The reaction time is subject to other conditions and cannot be generally specified. It is generally conducted for 0.2 to 10 hours. The pH range of the oligomer formation reaction is the same as the known interfacial reaction conditions, and the pH is often prepared to be above 10.
[0075] After obtaining a mixed solution of oligomers of a dihydric phenol (I) having a terminal chloroformate group, the present invention adds a hydroxyaryl-terminated polydiorganosiloxane (II) represented by the general formula (3) which is highly purified to have a molecular weight distribution (Mw / Mn) of 3 or less to the dihydric phenol (I) while stirring the mixed solution, so that the hydroxyaryl-terminated polydiorganosiloxane (II) and the oligomer undergo interfacial polycondensation, thereby obtaining a polycarbonate-polydiorganosiloxane copolymer.
[0076]
[0077] (In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms, R9 and R 10 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number of 10 to 300. X is a divalent aliphatic group having 2 to 8 carbon atoms.
[0078] When performing the interfacial polycondensation reaction, an acid binder can be appropriately added in consideration of the stoichiometric ratio (equivalent) of the reaction. As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide, potassium hydroxide, an alkali metal carbonate such as sodium carbonate, potassium carbonate, an organic base such as pyridine, or a mixture thereof, etc. can be used. Specifically, when a part of the hydroxyaryl-terminated polydiorganosiloxane (II) or the dihydric phenol (I) as described above is added to the reaction stage as a post-addition monomer, it is preferred to use 2 equivalents of a base or an excess amount of a base relative to the total molar number (usually 1 mole is equivalent to 2 equivalents) of the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) of the post-addition component.
[0079] The polycondensation by the interfacial polycondensation reaction of the oligomer of the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) is carried out by vigorously stirring the mixed liquid.
[0080] In the above-mentioned polymerization reaction, an end-capping agent or a molecular weight regulator is usually used. As the end-capping agent, compounds having monophenolic hydroxyl groups can be cited, and in addition to common phenol, p-tert-butylphenol, p-cumylphenol, tribromophenol, etc., long-chain alkylphenols, aliphatic acid chlorides, aliphatic carboxylic acids, hydroxybenzoic acid alkyl esters, hydroxyphenyl alkyl esters, alkyl ether phenols, etc. can also be exemplified. The amount used is 100 to 0.5 moles, preferably 50 to 2 moles, relative to 100 moles of all diphenol compounds used. Of course, two or more compounds can also be used in combination.
[0081] In order to promote the polycondensation reaction, a catalyst such as a tertiary amine such as triethylamine or a quaternary ammonium salt may be added.
[0082] The reaction time of the above polymerization reaction is preferably 30 minutes or longer, more preferably 50 minutes or longer. A small amount of an antioxidant such as sodium sulfite or hydrogen sulfide may be added as needed.
[0083] A branching agent can be used together with the above-mentioned dihydric phenolic compound to form a branched polycarbonate-polydiorganosiloxane. Examples of the trifunctional or higher polyfunctional aromatic compound used in the above-mentioned branched polycarbonate-polydiorganosiloxane copolymer resin include phloroglucinol, pentahydroxybiphenyl, or 4,6-dimethyl-2,4,6-tris(4-hydroxydiphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)ethane, )-4-methylphenol, 4-{4-[1,1-bis(4-hydroxyphenyl)ethyl]benzene}-α,α-dimethylbenzylphenol and other triphenols, tetrakis(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, or trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid and acid chlorides thereof, among which 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred. The ratio of the multifunctional compound in the branched polycarbonate-polydiorganosiloxane copolymer resin is preferably 0.001 to 1 mol%, more preferably 0.005 to 0.9 mol%, further preferably 0.01 to 0.8 mol%, and particularly preferably 0.05 to 0.4 mol% based on the total amount of the polycarbonate-polydiorganosiloxane copolymer resin. 1 It was calculated by H-NMR measurement.
[0084] The reaction pressure may be any of reduced pressure, normal pressure, and increased pressure, and may be appropriately carried out under normal pressure or the self-pressure of the reaction system. The reaction temperature is selected from the range of -20 to 50°C. In many cases, heat is generated with polymerization, so water cooling or ice cooling is preferred. The reaction time varies depending on other conditions such as the reaction temperature, and cannot be generally specified, but is usually carried out for 0.5 to 10 hours.
[0085] Depending on the circumstances, the obtained polycarbonate-polydiorganosiloxane copolymer resin may be appropriately subjected to physical treatment (mixing, classification, etc.) and / or chemical treatment (polymerization reaction, crosslinking treatment, partial decomposition treatment, etc.) to obtain a polycarbonate-polydiorganosiloxane copolymer resin having a desired reduced viscosity [ηSP / c].
[0086] The obtained reaction product (crude product) can be recovered as a polycarbonate-polydiorganosiloxane copolymer resin having a desired purity (degree of purification) by subjecting the obtained reaction product to various post-treatments such as known separation and purification methods.
[0087] The average size of the polydiorganosiloxane domains in the polycarbonate-polydiorganosiloxane copolymer resin molded article is preferably in the range of 1 to 40 nm. The above average size is more preferably 1 to 30 nm, and further preferably 5 to 25 nm. When it is less than the lower limit of the above preferred range, the impact resistance and flame retardancy cannot be fully exerted, and when it exceeds the upper limit of the above preferred range, the impact resistance may not be stably exerted.
[0088] The average domain size and normalized dispersion of the polydiorganosiloxane domains of the polycarbonate-polydiorganosiloxane copolymer resin molded product of the present invention are evaluated by small angle X-ray scattering (SAXS). Small angle X-ray scattering refers to a method for measuring diffuse reflection and diffraction generated in a small angle region within a scattering angle (2θ) of less than 10°. In the small angle X-ray scattering method, if there are regions with different electron densities of about 1 to 100 nm in a substance, the diffuse scattering of X-rays is measured based on the difference in electron density. The particle size of the measured object is calculated based on the scattering angle and the scattering intensity. In the case of a polycarbonate-polydiorganosiloxane copolymer resin having a cohesive structure in which polydiorganosiloxane domains are dispersed in a matrix of a polycarbonate polymer, diffuse scattering of X-rays is generated due to the difference in electron density between the polycarbonate matrix and the polydiorganosiloxane domains. The scattering intensity I at each scattering angle (2θ) within the range of scattering angle (2θ) less than 10° is measured in a small-angle X-ray scattering pattern. The polydiorganosiloxane domain is a spherical domain. It is assumed that there is a difference in particle size distribution. According to the assumed particle size and the assumed particle size distribution model, a commercially available analysis software is used for simulation to obtain the average size and particle size distribution (normalized dispersion) of the polydiorganosiloxane domain. According to the small-angle X-ray scattering method, the average size and particle size distribution of the polydiorganosiloxane domain dispersed in the matrix of the polycarbonate polymer, which cannot be accurately measured by observation using a transmission electron microscope, can be measured with high precision, simplicity and good reproducibility. The average domain size refers to the average value of the sizes of each domain. The normalized dispersion refers to a parameter obtained by normalizing the width of the particle size distribution using the average size. Specifically, it is a value obtained by normalizing the dispersion of the polydiorganosiloxane domain size using the average domain size, and is represented by the following formula (1).
[0089] Normalized dispersion (%) = δ / D av …(1)
[0090] In the above formula (1), δ is the standard deviation of the polydiorganosiloxane domain size, and Da is the average domain size.
[0091] The terms "average domain size" and "normalized dispersion" used in connection with the present invention refer to the values measured by measuring the 1.0 mm thickness portion of the three-layer plate produced by the method described in the examples using the above-mentioned small angle X-ray scattering method. In addition, the analysis is performed using an independent particle model that does not consider the interaction between particles (interparticle interference).
[0092] <Component A-2: ABS resin>
[0093] The ABS resin used as the A-2 component of the present invention is a copolymer obtained by grafting acrylonitrile and styrene with polybutadiene. As styrene, styrene and α-methylstyrene can be particularly preferably used. The proportion of the above-mentioned component grafted with polybutadiene is preferably 95 to 20% by weight, and particularly preferably 90 to 50% by weight in 100% by weight of the ABS resin component. In addition, relative to the total amount of 100% by weight of the above-mentioned acrylonitrile and styrene, it is preferred that acrylonitrile is 5 to 50% by weight and styrene is 95 to 50% by weight. In addition, part of the component grafted with the above-mentioned polybutadiene can also be mixed with (meth) methyl acrylate, ethyl acrylate, maleic anhydride, N-substituted maleimide, etc., and their content ratio in the ABS resin component is preferably 15% by weight or less. Further, the initiator, chain transfer agent, emulsifier, etc. used in the reaction can use various substances known in the past as needed. In the ABS resin of the present invention, the particle size of polybutadiene is preferably 0.1 to 5.0 μm, more preferably 0.2 to 3.0 μm, and particularly preferably 0.3 to 1.5 μm. The particle size distribution of the polybutadiene may be either a single distribution or a distribution having two or more peaks. In terms of morphology, the particles may be in a single phase or in a salami structure having an obstructing phase around the particles. In addition, as is known, ABS resin contains a copolymer composed of acrylonitrile and styrene not grafted to a diene rubber component, and the ABS resin of the present invention may also contain a free polymer component generated during the polymerization. The reduced viscosity of the free copolymer composed of acrylonitrile and styrene is preferably 0.2 to 1.0 dl / g, more preferably 0.3 to 0.7 dl / g, in terms of reduced viscosity (30°C). In addition, the ratio of grafted acrylonitrile and styrene to polybutadiene is preferably 20 to 200%, more preferably 20 to 70%, expressed as a grafting rate (wt%). The ABS resin can be manufactured by any method of bulk polymerization, suspension polymerization, and emulsion polymerization, and is particularly preferably manufactured by bulk polymerization. In the case of bulk polymerization, it does not substantially contain alkali metal salts from emulsifiers, etc., so the thermal stability of the resin composition can be better maintained. In addition, the copolymerization method can be a one-step copolymerization or a multi-step copolymerization. In addition, it is also possible to preferably use a blend of a vinyl compound polymer obtained by copolymerizing acrylonitrile and styrene in the ABS resin obtained by the above-mentioned manufacturing method.
[0094] <Component A-3: Polyester resin>
[0095] The polyester resin used as the component A-3 of the present invention is preferably a polyester resin in which 70 mol % or more of 100 mol % of the dicarboxylic acid components in the dicarboxylic acid components and diol components forming the polyester are aromatic dicarboxylic acids, more preferably 90 mol % or more, and most preferably 99 mol % or more.
[0096] Examples of the dicarboxylic acid include terephthalic acid, isophthalic acid, 2-chloroterephthalic acid, 2,5-dichloroterephthalic acid, 2-methylterephthalic acid, 4,4-stilbene dicarboxylic acid, 4,4-biphenyl dicarboxylic acid, phthalic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, dibenzoic acid, bis(p-carboxyphenyl)methane, anthracene dicarboxylic acid, 4,4-diphenyl ether dicarboxylic acid, 4,4-diphenoxyethane dicarboxylic acid, 5-sodium sulfoisophthalate, and ethylene bis(p-terephthalic acid). These dicarboxylic acids may be used alone or in combination of two or more. In the polyester resin of the present invention, in addition to the above-mentioned aromatic dicarboxylic acids, less than 30 mol% of aliphatic dicarboxylic acid components may be copolymerized. Specific examples thereof include adipic acid, sebacic acid, azelaic acid, dodecanedioic acid, 1,3-cyclohexane dicarboxylic acid, and 1,4-cyclohexane dicarboxylic acid.
[0097] As the diol component of the present invention, for example, ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2,2-dimethyl-1,3-propylene glycol, trans- or cis-2,2,4,4-tetramethyl-1,3-cyclobutanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, decamethylene glycol, cyclohexanediol, p-xylene glycol, bisphenol A, tetrabromobisphenol A, tetrabromobisphenol A-bis(2-hydroxyethyl ether), etc. can be mentioned. These can be used alone or in combination of two or more. It should be noted that the dihydric phenol in the diol component is preferably 30 mol% or less.
[0098] Specific examples of the polyester resin include polyethylene terephthalate (PET), polytrimethylene terephthalate, polybutylene terephthalate (PBT), polyethylene terephthalate, polyethylene naphthalate (PEN), polybutylene naphthalate (PBN), polyethylene-1,2-bis(phenoxy)ethane-4,4′-dicarboxylate, and copolymerized polyester resins such as polyethylene isophthalate / polyethylene terephthalate copolymers and polybutylene terephthalate / polybutylene isophthalate copolymers.
[0099] In addition, the terminal group structure of the polyester resin used in the present invention is not particularly limited, and the ratio of the hydroxyl group to the carboxyl group in the terminal group may be substantially equal, or the ratio of one side may be greater. In addition, these terminal groups may be capped by reacting a reactive compound with the terminal groups.
[0100] The method for producing the polyester resin used in the present invention is carried out by polymerizing the dicarboxylic acid component and the diol component while heating in the presence of a polycondensation catalyst containing titanium, germanium, antimony, etc., and discharging the by-product water or lower alcohol to the outside of the system. For example, as a germanium-based polymerization catalyst, germanium oxides, hydroxides, halides, alcohol salts, phenol salts, etc. can be exemplified, and more specifically, germanium oxide, germanium hydroxide, germanium tetrachloride, tetramethoxygermanium, etc. can be exemplified. In addition, in the present invention, compounds such as manganese, zinc, calcium, and magnesium used in the ester exchange reaction, which is the previous stage of the known polycondensation, can be used together, and after the ester exchange reaction is completed, the above catalyst can be deactivated using a phosphoric acid or phosphorous acid compound, etc. and polycondensation can be carried out. In addition, the method for producing the polyester resin also has any method of adopting a batch type or a continuous polymerization type.
[0101] Among the above polyester resins, polyethylene terephthalate is particularly preferred. The polyethylene terephthalate of the present invention is a polymer obtained by polycondensation of terephthalic acid or its derivatives and 1,4-ethanediol or its derivatives, but also includes copolymers obtained by copolymerization of other dicarboxylic acid components and other alkylene glycol components as described above.
[0102] The terminal group structure of polyethylene terephthalate is the same as above, and is not particularly limited. It is more preferred that the terminal carboxyl group is less than the terminal hydroxyl group. In addition, the manufacturing method can also adopt the various methods mentioned above, preferably the continuous polymerization method. This is because: its quality stability is high, and it is also cost-effective. In addition, as a polymerization catalyst, an organic titanium compound is preferably used. The reason is that there is a tendency to have less influence on ester exchange reactions, etc. As the above-mentioned organic titanium compound, as preferred specific examples, titanium tetrabutoxide, titanium isopropoxide, titanium oxalate, titanium acetate, titanium benzoate, titanium trimellitate, the reaction product of tetrabutyl titanate and trimellitic anhydride, etc. can be cited. The amount of the organic titanium compound used is preferably such that the titanium atom is in a ratio of 3 to 12 mg atomic % relative to the acid component constituting polyethylene terephthalate.
[0103] The molecular weight of the polyester resin of the present invention is not particularly limited, but the intrinsic viscosity measured at 35° C. using o-chlorophenol as a solvent is preferably 0.5 to 1.5, particularly preferably 0.6 to 1.2.
[0104] <Component A-4: AS resin>
[0105] The AS resin used as the A-4 component of the present invention is a copolymer of acrylonitrile and styrene. The AS resin can also be a copolymer having high stereoregularity such as syndiotactic styrene by using a catalyst such as a metallocene catalyst during its production. In addition, depending on the circumstances, polymers and copolymers having a narrow molecular weight distribution, block copolymers, and polymers and copolymers having high stereoregularity obtained by methods such as anionic living polymerization and free radical living polymerization can also be used.
[0106] <Component A-5: PS resin>
[0107] The PS resin used as the component A-5 of the present invention is a polymer of styrene.
[0108] <Component A-6: AAS resin>
[0109] The AAS resin used as the A-6 component of the present invention is a copolymer composed of acrylonitrile, styrene, and an acrylic rubber component.
[0110] <Component B: Acid phosphate ester>
[0111] The acidic phosphate used in the present invention can use phosphate monoesters, phosphate diesters, phosphate triesters and mixtures, preferably a mixture of monoesters and diesters. The number of carbon atoms of the ester can be used in various combinations within 1 to 22, and acid phosphate stearate is most preferred. The acid value of the acidic phosphate is 10 to 200 mgKOH / g, preferably 120 to 180 mgKOH / g, and more preferably 150 to 170 mgKOH / g. When the acid value is less than 10 mgKOH / g, it is not realistic to manufacture it as an acidic phosphate. When the acid value is greater than 200 mgKOH / g, it is impossible to prevent discoloration and strength reduction during molding. The acid value is determined using a potentiometric titration apparatus, and the alcohol solution of the acidic phosphate is titrated using a KOH alcohol solution.
[0112] The content of component B is 0.001 to 1 part by weight, preferably 0.01 to 0.1 part by weight, and more preferably 0.01 to 0.07 part by weight relative to 100 parts by weight of component A. When the content of component B is less than 0.001 part by weight or exceeds 1 part by weight, discoloration and strength reduction during molding cannot be prevented.
[0113] <Other ingredients>
[0114] The thermoplastic resin composition of the present invention may contain the following inorganic filler (component C), flame retardant (component D), anti-dripping agent (component E), and other additives within a range not impairing the purpose of the present invention.
[0115] <Component C: Inorganic filler>
[0116] The inorganic filler of component C can use conventionally known inorganic fillers, among which preferably at least one inorganic filler selected from the group consisting of (C-1) glass fiber (component C-1), (C-2) plate-shaped glass filler (component C-2), (C-3) fibrous carbon filler (component C-3), (C-4) non-fibrous carbon filler (component C-4) and (C-5) silicate mineral (component C-5).
[0117] The content of component C is preferably 1 to 150 parts by weight, more preferably 3 to 140 parts by weight, and further preferably 5 to 130 parts by weight relative to 100 parts by weight of component A. When the content of component C is less than 1 part by weight, sufficient rigidity may not be obtained, and when it exceeds 150 parts by weight, strength and flame retardancy during molding may be reduced.
[0118] <C-1 component: glass fiber>
[0119] The glass fiber used in the present invention is not particularly limited to the glass composition of A glass, C glass, E glass, etc., and may contain components such as TiO2, SO3, P2O5, etc. according to the circumstances. Among them, E glass (alkali-free glass) is more preferred when combined with a thermoplastic resin. In addition, two or more of these glass fibers may be used in combination. Glass fiber is a fiber made by rapidly cooling molten glass while stretching it using various methods and forming it into a specified fibrous or ground state. The rapid cooling and stretching conditions in the above case are not particularly limited. In addition, the cross-sectional shape may be an elliptical, cocoon-shaped, trilobal, or other shapes other than a perfect circle, in addition to a perfect circle. In addition, it may be a glass fiber that is a mixture of a perfect circular glass fiber and a glass fiber of a shape other than a perfect circle. Among them, a perfect circular glass fiber is more preferred.
[0120] In addition, in order to obtain a better mechanical strength, it is preferred that these glass fibers be pretreated with coupling agents such as isocyanate compounds, organic silane compounds, organic titanate compounds, organic borane compounds and epoxy compounds, and in the case of swellable layered silicates, they be pretreated with organic onium ions. The glass fibers used in the present invention preferably have a diameter (D) of 6 to 13 μm, a cut length (L) of 30 μm to 9 mm, and an L / D ratio of 2.3 to 1500.
[0121] <C-2; Plate glass filling material>
[0122] Examples of the plate-shaped glass filler include glass flakes, glass flakes coated with metals, and glass flakes coated with metal oxides.
[0123] The glass flakes as the matrix of the plate-shaped glass filler are plate-shaped glass fillers manufactured by methods such as a cylinder blowing method and a sol-gel method. The size of the raw material of the above-mentioned glass flakes can also be selected in various sizes according to the degree of crushing and classification. The average particle size of the glass flakes used in the raw material is preferably 10 to 1000 μm, more preferably 20 to 500 μm, and further preferably 30 to 300 μm. This is because the glass flakes in the above range are excellent in both handling and molding processability. Usually, the plate-shaped glass filler breaks due to the melt kneading process with the resin, and its average particle size becomes smaller. The number average particle size of the plate-shaped glass filler in the thermoplastic resin composition is preferably 10 to 200 μm, more preferably 15 to 100 μm, and further preferably 20 to 80 μm. It should be noted that the above-mentioned number average particle size is a value calculated by an image analyzer using an optical microscope observation of the residue of the plate-shaped glass filler taken during the high-temperature ashing of the molded product, the dissolution based on the solvent, and the decomposition based on the reagent. In addition, when calculating this value, the value is obtained by not counting the length of the scale thickness below the standard value. In addition, as the thickness, it is preferably 0.5 to 10 μm, more preferably 1 to 8 μm, and further preferably 1.5 to 6 μm. The plate-shaped glass filler having the above number average particle size and thickness sometimes achieves good mechanical strength, appearance, and molding processability.
[0124] The glass composition of the plate-shaped glass filling material can be applied to various glass compositions represented by A glass, C glass and E glass, etc., without special limitation. The above-mentioned glass filling material may also contain components such as TiO2, SO3 and P2O5 as needed. Among them, E glass (alkali-free glass) is more preferred. In addition, the plate-shaped glass filling material is preferred because the mechanical strength is improved after surface treatment using a well-known surface treatment agent, such as a silane coupling agent, a titanate coupling agent or an aluminate coupling agent. In addition, the plate-shaped glass filling material is preferably a plate-shaped glass filling material that has been subjected to a bundling treatment with an olefin resin, a styrene resin, an acrylic resin, a polyester resin, an epoxy resin and a polyurethane resin. The amount of the bundling agent attached to the bundled plate-shaped glass filling material is preferably 0.5 to 8% by weight, and more preferably 1 to 4% by weight in 100% by weight of the plate-shaped glass filling material.
[0125] In addition, the plate-shaped glass filling material includes a plate-shaped glass filling material obtained by surface coating of different types of materials. As the above-mentioned same type of materials, metals and metal oxides can be preferably exemplified. As metals, silver, copper, nickel and aluminum can be exemplified. In addition, as metal oxides, titanium oxide, cerium oxide, zirconium oxide, iron oxide, aluminum oxide and silicon oxide can be exemplified. As the method for surface coating of the above-mentioned different types of materials, there is no particular limitation, for example, various known plating methods (for example, electroplating, electroless plating, hot dip plating, etc.), vacuum evaporation method, ion plating method, CVD method (for example, thermal CVD, MOCVD, plasma CVD, etc.), PVD method and sputtering method can be cited.
[0126] <Component C-3: Fibrous carbon filler>
[0127] As fibrous carbon filling materials, for example, carbon fiber, carbon fiber coated with metal, carbon milled fiber, vapor-grown carbon fiber and carbon nanotube can be cited. Carbon nanotubes can be any of a fiber diameter of 0.003 to 0.1 μm, a single layer, a double layer and a multilayer, preferably a multilayer (so-called MWCNT). Among them, carbon fiber and carbon fiber coated with metal are preferred in terms of excellent mechanical strength and the ability to impart good electrical conductivity. It should be noted that good electrical conductivity has become one of the important properties required of resin materials in digital precision instruments (such as digital still cameras) in recent years.
[0128] As carbon fiber, any one of cellulose, polyacrylonitrile and asphalt can be used. In addition, carbon fiber obtained by the following method can also be used, the method is performed without spinning through a non-melting process represented by a method such as spinning or molding a raw material composition composed of a polymer based on a methylene bond of an aromatic sulfonic acid or its salt and a solvent, followed by carbonization. In addition, any one of a general type, a medium elastic modulus type and a high elastic modulus type can be used. Among them, a polyacrylonitrile high elastic modulus type is particularly preferred. In addition, the average fiber diameter of the carbon fiber is not particularly limited, and is usually 3 to 15 μm, preferably 5 to 13 μm. Carbon fibers that maintain an average fiber diameter in the above range can sometimes exhibit good mechanical strength and fatigue properties without damaging the appearance of the molded product. In addition, the preferred fiber length of the carbon fiber is 60 to 500 μm, preferably 80 to 400 μm, and particularly preferably 100 to 300 μm, based on the number average fiber length in the thermoplastic resin composition. It should be noted that the above-mentioned number average fiber length is a value calculated by an image analysis device such as an optical microscope observation of the residue of the carbon fiber taken from the high-temperature incineration of the molded product, the dissolution based on the solvent, and the decomposition based on the reagent. Moreover, when calculating this value, it is a value obtained by a method in which the numerical value of the length below the fiber length is not counted. The aspect ratio of the carbon fiber is preferably in the range of 10 to 200, more preferably in the range of 15 to 100, and further preferably in the range of 20 to 50. The aspect ratio refers to the value obtained by dividing the average fiber length by the average fiber diameter.
[0129] In addition, in order to improve the adhesion with the matrix resin and improve the mechanical strength, the surface of the carbon fiber is preferably subjected to oxidation treatment. The oxidation treatment method is not particularly limited, and for example, preferably exemplified are: (1) a method of treating the fibrous carbon filler with an acid or an alkali or a salt thereof, or an oxidizing gas, (2) a method of calcining the fiber or fibrous carbon filler that can become a fibrous carbon filler at a temperature of 700° C. or higher in the presence of an inert gas containing an oxygen-containing compound, and (3) a method of heat-treating the fibrous carbon filler in the presence of an inert gas after oxidation treatment.
[0130] Metal-coated carbon fiber is a carbon fiber having a metal layer coated on the surface of the carbon fiber. Examples of the metal include silver, copper, nickel, and aluminum. Nickel is preferred from the perspective of the corrosion resistance of the metal layer. As a method for coating with metal, various methods described in the surface coating of different types of materials in the previous plate-shaped glass filler can be used. Among them, the plating method is preferably used. In addition, in the case of the above-mentioned metal-coated carbon fiber, for the carbon fiber as the starting material, the carbon fiber cited as the above-mentioned carbon fiber can be used. The thickness of the metal coating layer is preferably 0.1 to 1 μm, and more preferably 0.15 to 0.5 μm. More preferably, it is 0.2 to 0.35 μm.
[0131] The carbon fibers and metal-coated carbon fibers are preferably subjected to a bundling treatment using olefin resins, styrene resins, acrylic resins, polyester resins, epoxy resins, polyurethane resins, etc. In particular, fibrous carbon fillers treated with polyurethane resins and epoxy resins are preferred in the present invention because of their excellent mechanical strength.
[0132] <Component C-4: Non-fibrous carbon filler>
[0133] As non-fibrous carbon filler materials, for example, carbon black, graphite, fullerene, etc. can be cited. Among them, carbon black and graphite are preferred from the aspects of mechanical strength, moisture and heat resistance, and thermal stability. As carbon black, carbon black with a DBP oil absorption of 100ml / 100g to 500ml / 100g is preferred in terms of conductivity. For the above-mentioned carbon black, acetylene black and Ketjen black are generally available. Specifically, for example, DENKABLACK manufactured by Denki Kagaku Kogyo Co., Ltd., VULCAN XC-72 and BP-2000 manufactured by Cabot Corporation, Ketjen black EC and Ketjen black EC-600JD manufactured by Lion Corporation, etc. can be cited.
[0134] As graphite, natural graphite or various artificial graphites of the mineral name graphite can be utilized. As natural graphite, any one of earthy graphite, scaly graphite (also known as Vein Graphite of blocky graphite) and flake graphite (Flake Graphite) can also be used. In addition, artificial graphite is a graphite obtained by heat-treating amorphous carbon to artificially orient irregularly arranged tiny graphite crystals, and in addition to the artificial graphite generally used in carbon materials, it also includes floating graphite (kish graphite), decomposed graphite and pyrolytic graphite, etc. The artificial graphite generally used in carbon materials is usually manufactured by graphitization treatment with petroleum coke and coal-based pitch coke as main raw materials.
[0135] The graphite of the present invention may include expanded graphite that can be thermally expanded by a treatment represented by an acid treatment, or graphite that has been expanded. The particle size of the graphite is preferably in the range of 2 to 300 μm. The above-mentioned particle size is more preferably 5 to 200 μm, further preferably 7 to 100 μm, and particularly preferably 7 to 50 μm. By satisfying the above range, good mechanical strength and appearance of the molded product can sometimes be achieved. On the other hand, if the average particle size is less than 2 μm, the effect of improving the rigidity sometimes becomes smaller, and if the average particle size is greater than 300 μm, the impact resistance is significantly reduced, and sometimes the so-called floating of graphite becomes obvious on the surface of the molded product, which is not preferred.
[0136] The fixed carbon content of the graphite of the present invention is preferably 80% by weight or more, more preferably 90% by weight or more, and further preferably 98% by weight or more. In addition, the volatile components of the graphite of the present invention are preferably 3% by weight or less, more preferably 1.5% by weight or less, and further preferably 1% by weight or less.
[0137] The average particle size of graphite in the present invention refers to the particle size of graphite itself before it becomes a resin composition, and the particle size refers to a value determined by a laser diffraction / scattering method.
[0138] In addition, the graphite surface may be subjected to surface treatments such as epoxy treatment, urethane treatment, silane coupling treatment, and oxidation treatment to increase affinity with the thermoplastic resin, as long as the properties of the composition of the present invention are not impaired.
[0139] <C-5 component: silicate mineral>
[0140] As the inorganic filler in the present invention, silicate minerals composed of at least a metal oxide component and a SiO2 component can be cited, preferably orthosilicates, disilicates, cyclic silicates and chain silicates, etc. The silicate mineral takes a crystalline state, and further, the crystal can be any form that each silicate mineral can take, and in addition, the shape of the crystal can also take various shapes such as fibrous and plate-like.
[0141] Silicate minerals may be any compound of a composite oxide, an oxyacid salt (composed of an ionic lattice), or a solid solution. Furthermore, a composite oxide may be any combination of two or more single oxides, or any combination of two or more single oxides and oxyacid salts. Furthermore, a solid solution may be any solid solution of two or more metal oxides or a solid solution of two or more oxyacid salts. In addition, it may be a hydrate. The form of crystal water in the hydrate may be introduced as a hydrosilicate ion in the form of Si-OH, as a hydroxide ion (OH - ) is introduced into the metal cation in the form of ions, and is introduced into the gaps in the structure as H2O molecules.
[0142] As the silicate mineral, an artificially synthesized product corresponding to a natural product may be used. As the artificially synthesized product, a silicate mineral obtained by various conventionally known methods, for example, various synthesis methods utilizing solid state reaction, hydrothermal reaction, and ultrahigh pressure reaction may be used.
[0143] Specific examples of silicate minerals in the metal oxide components include the following: Here, the words in parentheses are names of minerals containing the above-mentioned silicate minerals as main components, and mean that the compounds in parentheses can be used as exemplified metal salts.
[0144] Examples of silicate minerals containing K2O as a component include K2O·SiO2, K2O·4SiO2·H2O, K2O·Al2O3·2SiO2 (potassium pyroxene), K2O·Al2O3·4SiO2 (leucite), and K2O·Al2O3·6SiO2 (orthoclase).
[0145] Examples of silicate minerals whose components include Na2O include Na2O·SiO2, and its hydrates, Na2O·2SiO2, 2Na2O·SiO2, Na2O·4SiO2, Na2O·3SiO2·3H2O, Na2O·Al2O3·2SiO2, Na2O·Al2O3·4SiO2 (pyroxene), 2Na2O·3CaO·5SiO2, 3Na2O·2CaO·5SiO2, and Na2O·Al2O3·6SiO2 (albite), etc.
[0146] Examples of silicate minerals whose components include Li2O include Li2O·SiO2, 2Li2O·SiO2, Li2O·SiO2·H2O, 3Li2O·2SiO2, Li2O·Al2O3·4SiO2 (petalite), Li2O·Al2O3·2SiO2 (eucryptite) and Li2O·Al2O3·4SiO2 (spodumene).
[0147] Examples of silicate minerals containing BaO as a component include BaO·SiO 2 , 2BaO·SiO 2 , BaO·Al 2 O 3 ·2SiO 2 (barium feldspar) and BaO·TiO 2 ·3SiO 2 (bentonite).
[0148] Examples of silicate minerals containing CaO as a component thereof include 3CaO·SiO2 (tricalcium silicate of cement clinker mineral), 2CaO·SiO2 (dicalcium silicate of cement clinker mineral), 2CaO·MgO·2SiO2 (magnesium calcite), 2CaO·Al2O3·SiO2 (calcium aluminum calcite), a solid solution of magnesium calcite and calcite (calcite), CaO·SiO2 (wollastonite (including both α-type and β-type)), CaO·MgO·2SiO2 (diopside), CaO·MgO·SiO2 (calcium olivine), 3CaO·MgO·2SiO2 (magnesium calcite), CaO·Al2O3·2SiO2 (calcium feldspar), 5CaO·6SiO2·5H2O (tobermorite, 5CaO·6SiO2·9H2O, etc.) and other hydrated tobermorite groups. hydrates of wollastonite such as 2CaO·SiO2·H2O (calcite), hydrates of wollastonite such as 6CaO·6SiO2·H2O (xonotlite), hydrates of whitsonite such as 2CaO·SiO2·2H2O (white calcium zeolite), CaO·Al2O3·2SiO2·H2O (hard calcium zeolite), CaO·FeO·2SiO2 (ferrocalcium pyroxene), 3CaO·2SiO (brown zircon), 3CaO·Al2O3·3SiO2 (grossular garnet), 3CaO·Fe2O3·3SiO2 (andradite), 6CaO·4Al2O3·FeO·SiO2 (pleochroite), as well as clinzoisite, carnelian, allantois, fenghuang stone, axestone, scroosite and common pyroxene, etc.
[0149] In addition, as a silicate mineral containing CaO as a component, Portland cement can be cited. The type of Portland cement is not particularly limited, and any of ordinary, early strength, super early strength, medium heat, sulfate-resistant, white, etc. can be used. Various mixed cements such as blast furnace cement, silica cement, fly ash cement, etc. can also be used as component C. In addition, as other silicate minerals containing CaO as a component, blast furnace slag, ferrite, etc. can be cited.
[0150] Examples of silicate minerals containing ZnO include ZnO·SiO2, 2ZnO·SiO2 (zinc garnet) and 4ZnO·2SiO2·H2O (hemimorphite). Examples of silicate minerals containing MnO include MnO·SiO2, 2MnO·SiO2, CaO·4MnO·5SiO2 (rhodonite) and galaxytolite. Examples of silicate minerals containing FeO include FeO·SiO2 (orthopyroxene), 2FeO·SiO2 (fayalite), 3FeO·Al2O3·3SiO2 (aluminum garnet) and 2CaO·5FeO·8SiO2·H2O (ferroactinolite).
[0151] Examples of silicate minerals containing CoO as a component include CoO·SiO 2 and 2CoO·SiO 2 .
[0152] Examples of silicate minerals containing MgO include MgO·SiO2 (talc, enstatite), 2MgO·SiO2 (forsterite), 3MgO·Al2O3·3SiO2 (pyrope), 2MgO·2Al2O3·5SiO2 (cordierite), 2MgO·3SiO2·5H2O, 3MgO·4SiO2·H2O (talc), 5MgO·8SiO2·9H2O (attapulgite), 4MgO·6SiO2·7 H2O (sepiolite), 3MgO·2SiO2·2H2O (chrysolite), 5MgO·2CaO·8SiO2·H2O (tremolite), 5MgO·Al2O3·3SiO2·4H2O (chlorite), K2O·6MgO·Al2O3·6SiO2·2H2O (phlogopite), Na2O·3MgO·3Al2O3·8SiO2·H2O (glaucophane), as well as magnesia tourmaline, anthophyllite, ferromagnesian amphibole, vermiculite, montmorillonite, etc.
[0153] Examples of silicate minerals containing Fe2O3 as a component include Fe2O3·SiO2 and the like.
[0154] Examples of silicate minerals containing ZrO 2 as a component include ZrO 2 ·SiO 2 (zircon) and AZS refractory materials.
[0155] Examples of silicate minerals whose components contain Al2O3 include Al2O3·SiO2 (sillimanite, andalusite, kyanite), 2Al2O3·SiO2, Al2O3·3SiO2, 3Al2O3·2SiO2 (mullite), Al2O3·2SiO2·2H2O (kaolinite), Al2O3·4SiO2·H2O (pyrophyllite), Al2O3·4SiO2·H2O (bentonite), K2O·3Na2O·4Al2O3·8SiO2 (nepheline), K2O·3Al2O3·6SiO2·2H2O (dolomite, sericite), K2O·6MgO·Al2O3·6SiO2·2H2O (phlogopite), various zeolites, fluorphlogopite and biotite, etc.
[0156] Among the above-mentioned silicate minerals, talc, mica, and wollastonite are particularly preferred because they have an excellent balance between rigidity and impact resistance, are excellent in moisture and heat resistance, thermal stability, and appearance, and are easily available.
[0157] <Component D: Flame retardant>
[0158] The flame retardant of component D may be various compounds known as flame retardants for polycarbonate resins, and preferably at least one flame retardant selected from the group consisting of (D-1) halogenated carbonate compounds (component D-1), (D-2) phosphate compounds (component D-2), (D-3) phosphazene compounds (component D-3), (D-4) metal sulfonates (component D-4), and (D-5) organosilicon compounds (component D-5).
[0159] The content of component D is preferably 0.01 to 25 parts by weight, more preferably 0.015 to 22 parts by weight, and further preferably 0.02 to 20 parts by weight relative to 100 parts by weight of component A. When the content of component C is 0.01 to 25 parts by weight, it is sometimes possible to have both a sufficient effect of improving flame retardancy and an effect of preventing strength reduction during molding.
[0160] <Component D-1: Halogenated carbonate compound>
[0161] As the halogenated carbonate compound used in the present invention, it is preferred to use a halogenated carbonate compound in which the constituent unit represented by the following general formula (4) accounts for at least 60 mol % of all constituent units and the specific viscosity is 0.015 to 0.1.
[0162]
[0163] [In the general formula (4), X is a halogen atom, and R is an alkylene group having 1 to 4 carbon atoms, an alkylidene group having 1 to 4 carbon atoms, or -SO2-.]
[0164] In the above formula (4), R preferably represents a methylene group, an ethylene group, an isopropylidene group, or -SO2-, and particularly preferably represents an isopropylidene group. In addition, X is preferably a bromine atom.
[0165] The halogenated carbonate compound preferably has a small amount of residual chloroformate terminal and a terminal chlorine content of 0.3 ppm or less, and more preferably 0.2 ppm or less. The terminal chlorine content can be obtained by dissolving the sample in dichloromethane, adding 4-(p-nitrobenzyl)pyridine to react with the terminal chlorine (terminal chloroformate), and measuring it using an ultraviolet visible spectrophotometer (U-3200 manufactured by Hitachi, Ltd.). If the terminal chlorine content is less than 0.3 ppm, the thermal stability of the polycarbonate resin composition becomes better, and high-temperature molding can be performed. As a result, a resin composition with better molding processability can sometimes be provided.
[0166] In addition, the halogenated carbonate compound preferably has fewer residual hydroxyl terminals. More specifically, the amount of terminal hydroxyl groups is preferably 0.0005 mol or less, and more preferably 0.0003 mol or less, relative to 1 mol of the constituent units of the halogenated carbonate compound. The amount of terminal hydroxyl groups can be determined by dissolving the sample in deuterated chloroform and using 1 The amount of terminal hydroxyl groups can be determined by measuring with an H-NMR method. If the amount of terminal hydroxyl groups is the above, the thermal stability of the polycarbonate resin composition may be further improved.
[0167] The specific viscosity of the halogenated carbonate compound is preferably in the range of 0.015 to 0.1, more preferably in the range of 0.015 to 0.08. The specific viscosity of the halogenated carbonate compound is calculated according to the calculation formula used when calculating the viscosity average molecular weight of the polycarbonate resin as the component A-1 of the present invention.
[0168] The halogenated carbonate compounds are commercially available, for example, tetrabromobisphenol A carbonate oligomers (trade names FG-7000 and FG-8500) manufactured by Teijin Ltd., and these can be used in the present invention.
[0169] <Component D-2: Phosphate ester compound>
[0170] The phosphoric acid ester compound used in the present invention refers to a phosphoric acid ester compound other than the component B, and is preferably a phosphoric acid ester compound, particularly an aryl phosphoric acid ester compound.
[0171] The phosphate compound preferably has a molecular weight of 300 or more. If the molecular weight is less than 300, the difference between the boiling point of the phosphate compound and the combustion temperature of the resin composition becomes large, and the phosphate compound may volatilize more during combustion, thereby reducing the effect as a flame retardant.
[0172] As the phosphate compound, various phosphate compounds known in the art as flame retardants can be used, and more preferably, one or more phosphate compounds represented by the following general formula (5) can be used.
[0173]
[0174] (In the general formula (5), X is a dihydric phenol residue derived from a dihydroxy compound selected from the group consisting of hydroquinone, resorcinol, bis(4-hydroxydiphenyl)methane, bisphenol A, dihydroxydiphenyl, dihydroxynaphthalene, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ketone and bis(4-hydroxyphenyl)sulfide, n is an integer of 0 to 5, or in the case of a mixture of phosphates having different n numbers, it is the average value thereof, and R 1 , R 2 , R 3 and R 4 Each is independently a monohydric phenol residue derived from an aromatic group selected from phenol, cresol, xylenol, isopropylphenol, butylphenol and p-cumylphenol.)
[0175] The phosphate compound of the above general formula may be a mixture of compounds having different n numbers. In the case of the above mixture, the average n number is preferably 0.5 to 1.5, more preferably 0.8 to 1.2, further preferably 0.95 to 1.15, and particularly preferably in the range of 1 to 1.14.
[0176] Preferred specific examples of the dihydric phenol from which X in the general formula (5) is derived include resorcinol, bisphenol A, and dihydroxydiphenyl. Among them, resorcinol and bisphenol A are preferred.
[0177] As R in the above general formula (5) 1 , R 2 , R 3 and R 4 Preferred specific examples of the monohydric phenol include phenol, cresol, xylenol, and 2,6-dimethylphenol. Among them, phenol and 2,6-dimethylphenol are preferred.
[0178] Specific examples of the phosphate compound represented by the general formula (5) are preferably monophosphate compounds such as triphenyl phosphate and tris(2,6-xylyl)phosphate, and phosphate oligomers mainly composed of resorcinol bis[di(2,6-xylyl)phosphate], phosphate oligomers mainly composed of 4,4-dihydroxydiphenylbis(diphenyl phosphate), and phosphate oligomers mainly composed of bisphenol A bis(diphenyl phosphate). Among them, phosphate oligomers mainly composed of resorcinol bis[di(2,6-xylyl)phosphate], phosphate oligomers mainly composed of 4,4-dihydroxydiphenylbis(diphenyl phosphate), and phosphate oligomers mainly composed of bisphenol A bis(diphenyl phosphate) are preferred.
[0179] <Component D-3: Phosphazene compound>
[0180] The phosphazene compound used in the present invention is not particularly limited as long as it is a compound that does not contain halogen atoms and has a phosphazene structure in the molecule. The phosphazene structure referred to here refers to a structure represented by the formula: -P(R2)=N- [wherein R2 is an organic group]. Phosphazenes are represented by general formulas (6) and (7).
[0181]
[0182] (In the general formulae (6) and (7), X1, X2, X3, and X4 represent hydrogen, a hydroxyl group, an amino group, or an organic group containing no halogen atom. In addition, n represents an integer of 3 to 10.)
[0183] In the above general formulae (6) and (7), examples of the organic group not containing a halogen atom represented by X1, X2, X3, and X4 include alkoxy, phenyl, amino, and allyl groups. Among them, the cyclic phenoxyphosphazene represented by the following general formula (8) is preferred.
[0184]
[0185] [In the general formula (8), m represents an integer of 3 to 25. Ph represents a phenyl group.]
[0186] Examples of commercially available products of the phosphazene compound include SPS-100, SPR-100, SA-100, SPB-100, and SPB-100L (all manufactured by Otsuka Chemical Co., Ltd.), and FP-100 and FP-110 (all manufactured by Fushimi Pharmaceutical Co., Ltd.).
[0187] <Ingredient D-4: Metal sulfonate>
[0188] The metal used in the metal sulfonate used in the present invention is preferably an alkali metal or an alkaline earth metal, and more preferably an alkali metal. Examples of the alkali metal include lithium, sodium, potassium, rubidium, and cesium, and examples of the alkaline earth metal include beryllium, magnesium, calcium, strontium, and barium, and lithium, sodium, and potassium are particularly preferred.
[0189] The sulfonic acid used in the metal sulfonate used in the present invention is preferably an organic sulfonic acid, and more preferably an aliphatic sulfonic acid or an aromatic sulfonic acid.
[0190] The aliphatic sulfonic acid is preferably an alkylsulfonic acid, more preferably a fluoroalkylsulfonic acid in which a part or all of the alkyl groups are substituted with fluorine atoms, and most preferably a perfluoroalkylsulfonic acid in which all of the fluorine atoms are substituted. Preferred examples of perfluoroalkylsulfonic acids include perfluoromethanesulfonic acid, perfluoroethanesulfonic acid, perfluoropropanesulfonic acid, perfluorobutanesulfonic acid, perfluoromethylbutanesulfonic acid, perfluorohexanesulfonic acid, perfluoroheptanesulfonic acid, and perfluorooctanesulfonic acid, and particularly preferably one having 1 to 8 carbon atoms. These can be used alone or in combination of two or more.
[0191] Examples of the aromatic sulfonic acid include at least one acid selected from the group consisting of monomeric or polymeric sulfonic acids of aromatic sulfides, sulfonic acids of aromatic carboxylic acids and esters, monomeric or polymeric sulfonic acids of aromatic ethers, sulfonic acids of aromatic sulfonic esters, monomeric or polymeric aromatic sulfonic acids, monomeric or polymeric sulfonic acids of aromatic sulfones, sulfonic acids of aromatic ketones, heterocyclic sulfonic acids, sulfonic acids of aromatic sulfoxides, and condensates of aromatic sulfonic acids based on methylene bonds. These may be used alone or in combination of two or more.
[0192] <Component D-5: Silicone compound>
[0193] The organosilicon compound used in the present invention preferably has a highly active group, and preferred examples thereof include an alkoxy group or a Si-H group. The content ratio of the above groups is preferably in the range of 0.1 to 1.2 mol / 100 g, more preferably in the range of 0.12 to 1 mol / 100 g, and further preferably in the range of 0.15 to 0.6 mol / 100 g. The above ratio can be obtained by measuring the amount of hydrogen or alcohol generated per unit weight of the organosilicon compound by an alkali decomposition method.
[0194] The alkoxy group is preferably an alkoxy group having 1 to 4 carbon atoms, and a methoxy group is particularly preferred.
[0195] Generally, the structure of an organosilicon compound is formed by arbitrarily combining the following four types of siloxane units. That is, M unit: (CH3)3SiO 1 / 2 、H(CH3)2SiO 1 / 2 、H2(CH3)SiO 1 / 2 、(CH3)2(CH2=CH)SiO 1 / 2 、(CH3)2(C6H5)SiO 1 / 2 、(CH3)(C6H5)(CH2=CH)SiO 1 / 2 Monofunctional siloxane units such as (CH3)2SiO, H(CH3)SiO, H2SiO, H(C6H5)SiO, (CH3)(CH2=CH)SiO, (C6H5)2SiO, etc. Difunctional siloxane units such as (CH3)SiO 3 / 2、(C3H7)SiO 3 / 2 ,HSiO 3 / 2 、(CH2=CH)SiO 3 / 2 、(C6H5)SiO 3 / 2 Q unit: a trifunctional siloxane unit represented by SiO2.
[0196] Specifically, as representative formulas, the structure of the organosilicon compound used in the organosilicon flame retardant includes Dn, Tp, MmDn, MmTp, MmQq, MmDnTp, MmDnQq, MmTpQq, MmDnTpQq, DnTp, DnQq, and DnTpQq. Among them, the preferred structures of the organosilicon compound are MmDn, MmTp, MmDnTp, and MmDnQq, and the more preferred structure is MmDn or MmDnTp.
[0197] Here, the coefficients m, n, p, and q in the above-mentioned indicative formula represent the degree of polymerization of each siloxane unit, which is an integer greater than 1, and the sum of the coefficients in each indicative formula is the average degree of polymerization of the organosilicon compound. The average degree of polymerization is preferably in the range of 3 to 150, more preferably in the range of 3 to 80, further preferably in the range of 3 to 60, and particularly preferably in the range of 4 to 40. The more preferred range is, the better the flame retardancy becomes. Furthermore, as described later, the organosilicon compound containing a specified amount of aromatic groups also has excellent transparency and hue. As a result, good reflected light is obtained.
[0198] When any one of m, n, p, and q is a numerical value of 2 or more, the siloxane unit indicating the coefficient may be a siloxane unit having two or more different types of bonded hydrogen atoms and organic residues.
[0199] The organosilicon compound may be straight-chain or branched. In addition, the organic residue bonded to the silicon atom is preferably an organic residue having 1 to 30 carbon atoms, more preferably 1 to 20 carbon atoms. Specifically, examples of the above-mentioned organic residue include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and decyl, cycloalkyl groups such as cyclohexyl, aryl groups such as phenyl, and aralkyl groups such as tolyl. Alkyl groups, alkenyl groups, or aryl groups having 1 to 8 carbon atoms are further preferred. As the alkyl group, alkyl groups having 1 to 4 carbon atoms such as methyl, ethyl, and propyl groups are particularly preferred.
[0200] In addition, the organosilicon compound used as the organosilicon flame retardant preferably contains an aromatic group. On the other hand, the silane compound and the siloxane compound used as the organic surface treatment agent of the titanium dioxide pigment are obviously different from the organosilicon flame retardant in their preferred form in that they do not contain an aromatic group and obtain the desired effect. The more preferred organosilicon flame retardant is an organosilicon compound containing an aromatic group ratio (aromatic group amount) of 10 to 70% by weight (more preferably 15 to 60% by weight).
[0201] <Component E: Anti-drip agent>
[0202] As the anti-dripping agent used as the E component in the present invention, there can be mentioned a fluorine-containing polymer having fibril forming ability, and as the above-mentioned polymer, there can be mentioned polytetrafluoroethylene, tetrafluoroethylene copolymers (for example, tetrafluoroethylene / hexafluoropropylene copolymers, etc.), polycarbonate resins made of partially fluorinated polymers and fluorinated diphenols as disclosed in the gazette of U.S. Patent No. 4379910, etc. Among them, polytetrafluoroethylene (hereinafter sometimes referred to as PTFE) is preferred.
[0203] The molecular weight of PTFE with fibril forming ability has extremely high molecular weight, and shows the trend that PTFE adheres to each other into fibrous shape under the external force such as shearing force. Its molecular weight is 1 million to 10 million with the number average molecular weight obtained by standard specific gravity, and is more preferably 2 million to 9 million. The above-mentioned PTFE can also be used in the form of aqueous dispersion except solid form. In addition, the above-mentioned PTFE with fibril forming ability can also be used with the PTFE mixture in the mixed form of other resins to improve the dispersibility in the resin, and then obtain good flame retardancy and mechanical properties.
[0204] As commercial products of the above-mentioned PTFE having fibril forming ability, for example, Teflon (registered trademark) 6-J of Chemours-Mitsui Fluoroproducts Co., Ltd., Polyflon MPAFA500H and F-201 of Daikin Industries, Ltd., etc. As commercial products of aqueous dispersions of PTFE, Fluon D series manufactured by Daikin Industries, Ltd., Teflon (registered trademark) 31-JR of Chemours-Mitsui Fluoroproducts Co., Ltd., etc. can be cited as representatives.
[0205] As the mixed form of PTFE, those obtained by the following methods can be used, namely, (1) a method of mixing an aqueous dispersion of PTFE with an aqueous dispersion or solution of an organic polymer to obtain a co-coagulated mixture by coprecipitation (the method described in Japanese Unexamined Patent Publication Nos. 60-258263 and 63-154744, etc.), (2) a method of mixing an aqueous dispersion of PTFE with dried organic polymer particles (the method described in Japanese Unexamined Patent Publication No. 4-272957), (3) a method of uniformly mixing an aqueous dispersion of PTFE with a solution of organic polymer particles and A method of removing each medium from the above mixture at the same time (methods described in Japanese Patent Application Laid-Open No. 06-220210, Japanese Patent Application Laid-Open No. 08-188653, etc.), (4) a method of polymerizing monomers that form an organic polymer in an aqueous dispersion of PTFE (method described in Japanese Patent Application Laid-Open No. 9-95583), and (5) a method of uniformly mixing an aqueous dispersion of PTFE and an organic polymer dispersion, and then polymerizing a vinyl monomer in the mixed dispersion to obtain a mixture (method described in Japanese Patent Application Laid-Open No. 11-29679, etc.). Commercial products of these mixed forms of PTFE include "Metablen A3800" (trade name) and "Metablen A3750" of Mitsubishi Chemical Corporation.
[0206] The proportion of PTFE in the mixed form is preferably 1 to 60% by weight, more preferably 5 to 55% by weight, based on 100% by weight of the PTFE mixture. When the proportion of PTFE is within the above range, good dispersibility of PTFE may be achieved.
[0207] Examples of styrene monomers used as organic polymers for use in polytetrafluoroethylene-based mixtures include styrenes substituted with one or more groups selected from alkyl groups having 1 to 6 carbon atoms, alkoxy groups having 1 to 6 carbon atoms, and halogens, such as o-methylstyrene, m-methylstyrene, p-methylstyrene, dimethylstyrene, ethylstyrene, p-tert-butylstyrene, methoxystyrene, fluorostyrene, monobromostyrene, dibromostyrene, tribromostyrene, vinylxylene, and vinylnaphthalene, but are not limited thereto. The above styrene monomers may be used alone or in combination of two or more.
[0208] The acrylic monomer used as the organic polymer for the polytetrafluoroethylene-based mixture includes a (meth)acrylate derivative which may be substituted. Specifically, as the acrylic monomer, there can be exemplified (meth)acrylate derivatives which may be substituted with one or more groups selected from alkyl groups having 1 to 20 carbon atoms, cycloalkyl groups having 3 to 8 carbon atoms, aryl groups, and glycidyl groups, such as (meth)acrylonitrile, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, and glycidyl (meth)acrylate, maleimide which may be substituted with an alkyl group having 1 to 6 carbon atoms or an aryl group, such as maleimide, N-methyl-maleimide, and N-phenyl-maleimide, maleic acid, phthalic acid, and itaconic acid, but the present invention is not limited thereto. The acrylic monomers may be used alone or in combination of two or more. Among them, (meth)acrylonitrile is preferred.
[0209] In addition, as the anti-dripping agent in the present invention, coated branched PTFE can be used. The coated branched PTFE is a polytetrafluoroethylene system mixture consisting of branched polytetrafluoroethylene particles and organic polymers, and the outside of the branched polytetrafluoroethylene has a coating consisting of an organic polymer, preferably a polymer comprising units from styrene monomers and / or units from acrylic acid monomers. The above-mentioned coating is formed on the surface of the branched polytetrafluoroethylene. In addition, the above-mentioned coating preferably comprises a copolymer of styrene monomers and acrylic acid monomers.
[0210] The polytetrafluoroethylene contained in the coated branched PTFE is branched polytetrafluoroethylene. When the polytetrafluoroethylene contained is not branched polytetrafluoroethylene, the anti-drip effect when a small amount of polytetrafluoroethylene is added becomes insufficient. The branched polytetrafluoroethylene is in a granular form, preferably having a particle size of 0.1 to 0.6 μm, more preferably 0.3 to 0.5 μm, and further preferably 0.3 to 0.4 μm. Although the surface appearance of the molded article is excellent when the particle size is less than 0.1 μm, polytetrafluoroethylene having a particle size of less than 0.1 μm is difficult to obtain commercially. In addition, when the particle size is greater than 0.6 μm, the surface appearance of the molded article sometimes deteriorates. The number average molecular weight of the polytetrafluoroethylene used in the present invention is preferably 1×10 4 ~1×10 7 , more preferably 2×10 6 ~9×10 6 Generally, polytetrafluoroethylene with a high molecular weight is more preferred in terms of stability. It can be used in the form of a powder or a dispersion.
[0211] The content of branched polytetrafluoroethylene in the coated branched PTFE is preferably 20 to 60 parts by weight, more preferably 40 to 55 parts by weight, further preferably 47 to 53 parts by weight, particularly preferably 48 to 52 parts by weight, and most preferably 49 to 51 parts by weight, relative to 100 parts by weight of the total weight of the coated branched PTFE. When the ratio of the branched polytetrafluoroethylene is within the above range, good dispersibility of the branched polytetrafluoroethylene may be achieved.
[0212] The content of component E is preferably 0.05 to 3 parts by weight, more preferably 0.1 to 2 parts by weight, and further preferably 0.2 to 1.5 parts by weight relative to 100 parts by weight of component A. If it is greater than this range, not only will the cost rise, but also there is a situation where extrusion processability becomes insufficient. On the other hand, if it is less than this range, there is a situation where flame retardancy becomes insufficient and tensile strength also decreases. It should be noted that the ratio of the above-mentioned component E represents the net content of the anti-dripping agent, and in the case of PTFE in a mixed form, it represents the net content of PTFE.
[0213] <Production of thermoplastic resin composition>
[0214] Any method may be used to produce the thermoplastic resin composition of the present invention. For example, the following method may be used: after fully mixing component A, component B and any other components using a premixing mechanism such as a V-type mixer, a Henschel mixer, a mechanochemical device, an extrusion mixer, etc., the premix is granulated using an extrusion granulator, a briquetting machine, etc. as needed, and then melt-kneading is performed using a melt-kneading machine represented by a vented twin-screw extruder, and then pelletizing is performed using a granulator.
[0215] In addition, there can be mentioned a method of independently supplying each component to a melt kneading machine represented by a vented twin-screw extruder, a method of premixing a part of each component and then supplying it to a melt kneading machine independently with the remaining components, etc. As a method of premixing a part of each component, for example, there can be mentioned a method of premixing components other than component A in advance, and then mixing them in the thermoplastic resin of component A or directly supplying them to the extruder.
[0216] As a method of premixing, for example, when a component A includes a powdered component, the following method can be cited: a part of the above powder is blended with a formulated additive to produce a masterbatch of the additive diluted with the powder, and the above masterbatch is used. In addition, a method of independently supplying one component to a melt extruder from the middle can also be cited. It should be noted that when a liquid component is included in the formulated component, the supply to the melt extruder can use a so-called liquid injection device or liquid addition device.
[0217] As an extruder, it is preferred to use a device with an exhaust port that can degas the moisture in the raw material and the volatile gas produced by the melt-kneaded resin. It is preferably provided with a vacuum pump that is used to efficiently discharge the generated moisture and volatile gas to the outside of the extruder from the exhaust port. In addition, a wire mesh for removing foreign matter mixed into the extrusion raw material can also be provided in the area before the die portion of the extruder, and the foreign matter is removed from the resin composition. As the above-mentioned wire mesh, metal mesh, screen changer, sintered metal plate (disc filter, etc.) and the like can be cited.
[0218] Examples of the melt kneading machine include a Banbury mixer, a kneading roll, a single-screw extruder, and a multi-screw extruder having three or more screws, in addition to a twin-screw extruder.
[0219] The extruded resin as described above is directly cut and pelletized, or after forming a strand, the strand is cut and pelletized using a granulator. When it is necessary to reduce the influence of external dust and the like during pelletization, it is preferred to clean the atmosphere around the extruder. Furthermore, in the manufacture of the above-mentioned pellets, various methods that have been proposed in the polycarbonate resin for optical disks can be used to appropriately narrow the shape distribution of the pellets, reduce the amount of erroneous cuts, reduce the amount of fine powder generated during transportation or conveying, and reduce the amount of bubbles (vacuum bubbles) generated inside the strands and pellets. Through these treatment methods, high molding cycles and a reduction in the proportion of defects such as silver streaks can be achieved. In addition, the shape of the pellets can be a general shape such as a cylinder, a prism, and a sphere, and a cylinder is more preferred. The diameter of the above-mentioned cylinder is preferably 1 to 5 mm, more preferably 1.5 to 4 mm, and more preferably 2 to 3.3 mm. On the other hand, the length of the cylinder is preferably 1 to 30 mm, more preferably 2 to 5 mm, and more preferably 2.5 to 3.5 mm.
[0220] <Molding products>
[0221] The thermoplastic resin composition of the present invention can be manufactured into various products by injection molding the pellets usually obtained by the above method. In the above injection molding, not only the usual molding method can be used, but also the injection molding methods such as injection compression molding, injection stamping molding, gas-assisted injection molding, foam molding (including molding based on injection of supercritical fluid), insert molding, in-mold coating molding, heat-insulating metal mold molding, rapid heating and cooling metal mold molding, two-color molding, sandwich molding and ultra-high-speed injection molding can be used appropriately according to the purpose to obtain molded products. The advantages of these various molding methods are well known. In addition, molding can select any one of the cold runner method and the hot runner method.
[0222] The inventors of the present invention believe that the best current embodiments of the present invention include preferred ranges of the above-mentioned requirements, and representative examples thereof are described in the following examples. Of course, the present invention is not limited to these embodiments.
[0223] Example
[0224] Hereinafter, the present invention will be further described with reference to Examples, but the present invention is not limited thereto. It should be noted that the evaluation was carried out on the following items.
[0225] (i) Color change during retention
[0226] The pellets obtained from the various compositions of the examples were dried at 100°C using a hot air dryer for 5 hours, and then injection molded into a 150 mm × 150 mm × 2 mm square plate 100 times at the temperature in the table using an injection molding machine [Sumitomo Heavy Industries, Ltd. SG150U·S-MIV]. Then, the operation of the molding machine was interrupted to allow the resin to remain in the barrel. After 15 minutes, the square plate was molded again, and the hue of the square plate before and after retention was measured using a Tokyo Densho color analyzer TC-1800MKII, and the color difference (ΔE) before and after retention was calculated.
[0227] (ii) Strength retention during retention
[0228] A high-speed surface impact test was performed using the square plate used in "(i) Discoloration during retention", and the fracture energy of the square plate before and after retention was measured. The strength retention rate before and after retention was calculated by the following formula. It should be noted that the measurement was performed using Hydroshot HTM-1 manufactured by Shimadzu Corporation at 23°C and a test speed of 7 m / s.
[0229] Strength retention (%) = [fracture energy after retention / fracture energy before retention] × 100
[0230] (iii) Recyclability
[0231] The square plate before retention used in "(i) Discoloration during retention" was placed horizontally outdoors in the green district of Chiba City for one year, then crushed and reshaped into a square plate. The hue and breaking energy of the square plate before placement and the reshaped square plate were measured using the same method as "(i) Discoloration during retention" and "(ii) Strength retention during retention", and the color difference (ΔE) and strength retention of the two were calculated.
[0232] (iv) Flame retardancy
[0233] The pellets obtained from the compositions of the examples were dried at 100°C for 5 hours using a hot air dryer, and UL test pieces with a thickness of 1.5 mm were continuously molded at the temperature in the table using an injection molding machine [Sumitomo Heavy Industries, Ltd. SG150U·S-MIV]. According to the method described in UL94, they were classified into four types: V-0, V-1, V-2, and HB. If the flammability is so poor that it is not suitable for any classification, it is recorded as Not-V. It should be noted that the flame retardancy needs to be classified as any of V-0, V-1, V-2, and HB.
[0234] (v) Flexural modulus
[0235] The bending modulus value was measured using the test piece before retention used in "(i) Strength retention during retention".
[0236] [Examples 1-1 to 1-12, Examples 2-1 to 2-15, Examples 3-1 to 3-13, Comparative Examples 1-1 to 1-5, Comparative Examples 2-1 to 2-3, Comparative Examples 3-1 to 3-3]
[0237] According to the following method, a resin composition composed of the mixing ratios in Table 1, Table 2 and Table 3 is prepared. It should be noted that the symbols in the following table are used for explanation. Each component in the proportion in the table is weighed, mixed evenly using a roller, and the above mixture is put into an extruder to prepare the resin composition. The extruder uses a vented twin-screw extruder made by Nippon Steel Works: TEX-30XSST (fully meshed, co-rotating, double-threaded screw). It should be noted that the glass fiber, plate-shaped glass filler, and fibrous carbon filler in the inorganic filler are supplied from the second supply port, and the other components are supplied from the first supply port. The extrusion conditions are a discharge rate of 20 kg / h, a screw speed of 150 rpm, a vacuum degree of 3 kPa for exhaust, and an extrusion temperature of the temperature in the table. The obtained pellets are used to form test pieces for evaluation using an injection molding machine by the above method. The evaluation results are shown in Tables 1 to 3. It should be noted that the components recorded by the symbols in Tables 1 to 3 are as follows.
[0238] (Component A: thermoplastic resin)
[0239] A-1-1: Aromatic polycarbonate resin (polycarbonate resin powder having a viscosity average molecular weight of 20,700 produced from bisphenol A and phosgene by a conventional method, Panlite L-1225WS (product name) manufactured by Teijin Limited)
[0240] A-1-2: Modified polycarbonate resin powder with a viscosity average molecular weight of 22,300 obtained by the following method
[0241] A reactor equipped with a thermometer, a stirrer and a reflux cooler was charged with 4229 parts of a 48% sodium hydroxide aqueous solution and 20,000 parts of ion exchange water, 2191 parts of 1,1-bis(4-hydroxy-3-methylphenyl)propane (hereinafter abbreviated as Bis-1), 1951 parts of bisphenol A and 8.3 parts of sodium dithionite were dissolved therein, and then 11620 parts of dichloromethane were added, and 2200 parts of phosgene were blown into the mixture at 15 to 25° C. for about 60 minutes under stirring. After the blowing of phosgene was completed, 704 parts of a 48% sodium hydroxide aqueous solution and 102 parts of p-tert-butylphenol were added, and the mixture was stirred again. After emulsification, 4.32 parts of triethylamine were added, and the mixture was further stirred at 28 to 33° C. for 1 hour to terminate the reaction. After the reaction is completed, the product is diluted with dichloromethane and washed with water, then adjusted to acidity with hydrochloric acid and washed with water, and further washed with water repeatedly until the conductivity of the aqueous phase is almost equal to that of ion exchange water, thereby obtaining a dichloromethane solution of a polycarbonate resin. Next, the solution is passed through a filter with a mesh of 0.3 μm, and further dripped into warm water in a kneader with an isolation chamber having a foreign matter removal port at the bearing portion, and dichloromethane is distilled off to form scales of the polycarbonate resin, and then the liquid-containing scales are crushed and dried to obtain a powder.
[0242] A-1-3: Polycarbonate-polydiorganosiloxane copolymer resin (viscosity average molecular weight 19800, PDMS content 4.2%, PDMS polymerization degree 37)
[0243] A-2: ABS resin (SUNTAC AT-07 (trade name) manufactured by Japan A&L Co., Ltd., butadiene rubber component about 17.5% by weight, weight average rubber particle size 1.2 μm, manufactured by bulk polymerization)
[0244] A-3: Polyethylene terephthalate (TRN-8550FF (trade name) manufactured by Teijin Co., Ltd.)
[0245] A-4: AS resin (LITAC ABS-207 (trade name) manufactured by Japan A&L Co., Ltd.)
[0246] A-5: PS resin (GP-110 (trade name) manufactured by IRPC Public Company Limited)
[0247] A-6: AAS resin (777K (trade name) manufactured by INEOS)
[0248] (Component B: acid phosphate ester)
[0249] B-1: stearyl acid phosphate (AX-71 (trade name) manufactured by ADEKA Corporation, acid value 158 mgKOH / g)
[0250] B-2 (Comparative Example): Stearyl acid phosphate (A-18F (trade name) manufactured by SC Organic Chemical Co., Ltd., acid value 215 mgKOH / g)
[0251] B-3: Acid stearyl phosphate (mixture of B-1 and B-2 (weight ratio 1:1) acid value 187 mgKOH / g)
[0252] (Component C: Inorganic filler)
[0253] C-1: Glass fiber (3PE937 (product name) manufactured by Nitto Bosho Co., Ltd.)
[0254] C-2: Glass flake (MEG160FYX (product name) manufactured by Nippon Sheet Glass Co., Ltd.)
[0255] C-3: Carbon fiber (HT C493 (product name) manufactured by Teijin Limited)
[0256] C-4: Non-fibrous carbon filler (EN-250HT (product name) manufactured by Nishimura Graphite Co., Ltd.)
[0257] C-5: Talc (Victory Light TK-RC (product name) manufactured by Shengguangshan Mining Co., Ltd.)
[0258] (Component D: flame retardant)
[0259] D-1: Tetrabromobisphenol A carbonate oligomer (FG-7000 (product name) manufactured by Teijin Limited)
[0260] D-2: Phosphate ester containing resorcinol bis[di(2,6-dimethylphenyl)phosphate] as the main component (PX-200 (trade name) manufactured by Daihachi Chemical Industry Co., Ltd.)
[0261] D-3: Cyclic phenoxyphosphazene (FP-110 (trade name) manufactured by Fushimi Pharmaceutical Co., Ltd.)
[0262] D-4: Potassium perfluorobutanesulfonate (F-TOP KSBF (product name) manufactured by Mitsubishi Materials Corporation)
[0263] D-5: an organosiloxane flame retardant containing a Si—H group, a methyl group, and a phenyl group (X-40-2600J (trade name) manufactured by Shin-Etsu Chemical Co., Ltd.)
[0264] (Component E: anti-drip agent)
[0265] E-1: Polytetrafluoroethylene (Polyflon MPFA500B (trade name) manufactured by Daikin Industries, Ltd.)
[0266]
[0267]
[0268]
Claims
1. A thermoplastic resin composition comprising 0.001 to 1 part by weight of (B) an acidic phosphate having an acid value of 10 to 200 mgKOH / g (component B) based on 100 parts by weight of (A) a thermoplastic resin (component A).
2. The thermoplastic resin composition according to claim 1, wherein The (C) inorganic filler, ie, component C, is contained in an amount of 1 to 150 parts by weight based on 100 parts by weight of component A.
3. The thermoplastic resin composition according to claim 1 or 2, wherein The (D) flame retardant, that is, the component D, is contained in an amount of 0.01 to 25 parts by weight based on 100 parts by weight of the component A.
4. The thermoplastic resin composition according to any one of claims 1 to 3, wherein The (E) anti-dripping agent, that is, component E, is contained in an amount of 0.05 to 3 parts by weight based on 100 parts by weight of component A.
5. The thermoplastic resin composition according to any one of claims 1 to 4, wherein The component A is at least one thermoplastic resin selected from the group consisting of (A-1) a polycarbonate resin (component A-1), (A-2) an ABS resin (component A-2), (A-3) a polyester resin (component A-3), (A-4) an AS resin (component A-4), (A-5) a PS resin (component A-5), and (A-6) an AAS resin (component A-6).
6. The thermoplastic resin composition according to any one of claims 1 to 5, wherein The component A is at least one thermoplastic resin selected from the group consisting of (A-1) a polycarbonate resin (component A-1), (A-2) an ABS resin (component A-2), and (A-3) a polyester resin (component A-3).
7. The thermoplastic resin composition according to any one of claims 1 to 6, wherein The content of the component A-1 is 40 to 100 parts by weight based on 100 parts by weight of the component A.
8. The thermoplastic resin composition according to any one of claims 1 to 7, wherein Component B is stearyl acid phosphate.
9. The thermoplastic resin composition according to any one of claims 1 to 8, wherein The component C is at least one inorganic filler selected from the group consisting of (C-1) glass fiber, i.e., component C-1; (C-2) plate-shaped glass filler, i.e., component C-2; (C-3) fibrous carbon filler, i.e., component C-3; (C-4) non-fibrous carbon filler, i.e., component C-4; and (C-5) silicate mineral, i.e., component C-5.
10. The thermoplastic resin composition according to any one of claims 1 to 9, wherein The component D is at least one flame retardant selected from the group consisting of (D-1) a halogenated carbonate compound (component D-1), (D-2) a phosphate ester compound (component D-2), (D-3) a phosphazene compound (component D-3), (D-4) a metal sulfonate (component D-4), and (D-5) an organosilicon compound (component D-5).
11. A molded article comprising the thermoplastic resin composition according to any one of claims 1 to 10.
Citation Information
Patent Citations
JP1974083427A
Measuring device of differential pressure
JP1981040734A
Polymer powder composition containing tetrafluoroethylene polymer
JP1985258263A
Method for mixing fluoropolymer with polycarbonate
JP1988154744A
Polycarbonate having improved appearance and flame retardancy
JP1992272957A